Stomatal Conductance In Relation To Xylem Sap Abscisic Acid Concentration In Hopea Odorata Roxb. And Mlmusops Elengi Linn.Seedlings - Zainudin, S.R; Kamis, A (UKM, 2002)
Xylem sap ABA and leaf ABA of Hopea odorata and Mimusops elengi were measured under condition of soil compaction and drought and the role of ABA were investigated in the regulation of stomatal cooductance of these two species. A rapid and substantial increase in xylem sap abscisic acid (ABA) concentration rather than leaf ABA concentration, which was closely related to soil drying and stomatal conductance, was observed in both species. The increase in xylem sap ABA concentration observed at high bulk density was closely related with reductions of stomatal conductance. These results suggest that xylem ABA may act as a stress signal in the control of stomatal conductance. The inability of M elengi seedlings to produce as much xylem ABA concentration compared to H. odorata_seedlings in response to soil compaction and water stress may have been crucial to its Wlure to maintain near-normal rates of leaf expansion at certain critical level of compaction.